Design of experiment for in-situ synthesis of waste vegetable oils and synthetic based polyurethane (PU) foam composites - Abd Wahab, Hanani; Mohd Rus, Anika Zafiah; Zaliran, M. Taufiq (Science Publishing Corporation, 2018)
This study focused on fabrication of polyurethane (PU) foams and its composites based on hydroxylated bioepoxy (B) and petroleum based synthetic epoxy (E), crosslinker and wood fillers. The fabrication of foams: B and E with different wood filler size such as flake (L) and powder (P) on different composition ratios of 5%, 10%, 15% and 20%. The fabrication techniques used in this research are open moulding technique. The physical properties such as morphological pore structure and its homogeneity of wood filler distribution in foam polymer composites were measured. The effect of different size of wood filler loading in PU foam composites were analyzed and discussed in detail such as gelling time, main pore size, interconnected pore and struts thickness. The operatory conditions of in-situ PU foams synthesis were optimized using a design of experiment (DOE). The correlations between factors (X1, X2, X3) and the responses (Y1, Y2, Y3, Y4) for B, E as well as BL, BF, EL or EF foams were further analyzed using Minitab software.